Can technology-specific deployment policies be cost-effective? The case of renewable energy support schemes - Paul Lehmann; Patrik Söderholm (Helmholtz-Zentrum für Umweltforschung (UFZ), 2016)
While there is relatively limited disagreement on the general need for supporting the deployment of renewable energy sources for electricity generation (RES-E), there are diverging views on whether the granted support levels should be technology-neutral or technology-specific. In this paper we question the frequently stressed argument that technology-neutral schemes will promote RES-E deployment cost-effectively. A simple partial equilibrium model of the electricity sector with one representative investor is developed to illustrate how the cost-effective support levels to different RES-E technologies will be influenced when selected market failures are introduced. We address market failures associated with technological development, long-term risk taking, path dependencies as well as various external costs, all of which drive a wedge between the private and the social costs of RES-E deployment. Based on these analytical findings and a review of empirical literature, we conclude that the relevance of these market failures is typically heterogeneous across different RES-E technologies. The paper ends by discussing a number of possible caveats to implementing cost-effective technology-specific support schemes in practice, including the role of various information and political economy constraints. While these considerations involve important challenges, neither of them suggests an unambiguous plea for technology-neutral RES support policies either.
Keywords: H23; O33; Q42; 330; technology deployment; renewable energy sources; support schemes; cost-effectiveness